Their names to live : what the Vietnam Veterans Memorial means to America - Ashabranner, Brent K., 1921-; Ashabranner, Jennifer (Brookfield, Conn. Twenty-First Century Books, 1998)
Describes the planning and creation of the Vietnam Veterans Memorial and how it came to be a symbol for the dead of all American wars.
Includes bibliographical references (p. [61]-62) and index.
Keywords: Vietnam Veterans Memorial (Washington, D.C.) -- Juvenile literature; Vietnam Veterans Memorial (Washington, D.C.); National monuments